Influence analysis characteristics businessman, development human resources, and competence on the performance of Upanat sandal business actors in the Borobudur Area Magelang - Kussujaniatun, Sri; Hartati, Anis Siti (Indonesia Research and Study Center, 2026)
Upanat sandal are specialized footwear designed to reduce surface wear on the stone structure of Borobudur Temple. The sustainability of their production is closely related to the performance of local business actors involved in their manufacture. This study aims to analyze the influence of entrepreneurial characteristics, human resource development, and human resource competence on the performance of Upanat business actors in the Borobudur area, Magelang. This research employed a quantitative approach using primary data collected through questionnaires distributed to 40 Upanat entrepreneurs selected through random sampling. The data were analyzed using multiple linear regression analysis to examine the effect of each independent variable on business performance. The results show that entrepreneurial characteristics, human resource development, and human resource competence have a positive and significant effect on business performance. Among these variables, human resource competence has the strongest influence on the performance of Upanat business actors. These findings indicate that strengthening skills, knowledge, creativity, and technological capabilities is crucial for improving productivity and ensuring the sustainability of Upanat businesses in the Borobudur area.